(untitled) (Faculty of Education Scientific Journal, 2023)
In this research, we shall discuss the oscillation behavior of solutions for second order nonlinear differential equations. By employing a generalized Riccati transformation and an averaging technique, we derive some new oscillation conditions for all solutions. Our results are extention for some well known oscillation results. The relevance of our results is illustrated by some examples.